Three-year experience with combined treatment with alendronate and alfacalcidol in Japanese patients with severe bone loss and osteoporotic fracture - Iwamoto J; Sato Y; Uzawa M; Takeda T; Matsumoto H (Dove Medical Press, 2011)
Jun Iwamoto1, Yoshihiro Sato2, Mitsuyoshi Uzawa3, Tsuyoshi Takeda1, Hideo Matsumoto11Institute for Integrated Sports Medicine, Keio University School of Medicine, Tokyo, Japan; 2Department of Neurology, Mitate Hospital, Fukuoka, Japan; 3Department of Orthopaedic Surgery, Keiyu Orthopaedic Hospital, Gunma, JapanPurpose: Combined treatment with alendronate and alfacalcidol is more useful to increase bone mineral density (BMD) than alendronate or alfacalcidol alone. A retrospective study was conducted to investigate the 3-year outcome of combined treatment with alendronate and alfacalcidol in patients with severe bone loss (BMD ≤ 50% of the young adult mean) and osteoporotic fracture.Methods: Thirty-four patients (six men and 28 postmenopausal women) with primary or secondary osteoporosis who had been treated with alendronate and alfacalcidol for more than 3 years were analyzed. The lumbar spine or total hip BMD and bone turnover markers were monitored, and the incidence of osteoporotic fractures was assessed.Results: The urinary level of cross-linked N-terminal telopeptides of type I collagen and serum level of alkaline phosphatase significantly decreased (-42.5% at 3 months and -18.9% at 3 years), and the lumbar spine BMD, but not the total hip BMD, significantly increased (14.8% at 3 years), compared with the baseline values. However, the incidence of vertebral and nonvertebral fractures was 26.5% and 2.9%, respectively, suggesting a high incidence of vertebral fractures.Conclusion: The results of the present study suggest that combined treatment with alendronate and alfacalcidol may be useful to reduce bone turnover and increase the lumbar spine BMD in patients with severe bone loss and osteoporotic fracture. However, its efficacy against vertebral fractures appears not to be sufficient. Thus, anabolic agents such as teriparatide should be taken into consideration as first-line drugs in patients with severe osteoporosis.Keywords: osteoporosis, fragility fracture, bone mineral density, bone turnover